The new Oxford companion to law - Cane, Peter 1950-; Conaghan, Joanne (Oxford University Press, 2008)
Consisting in over 1,700 alphabetically arranged entries, the Companion features: the fundamentals of all the major areas of law such as criminal law, tax and social security law, human rights law, family and employment law, education law, sports law, international and EU law; the role and workings of legal institutions such as parliaments, courts, law schools, and international bodies such as the EU and the UN; leading cases, famous trials and distinguished lawyers, past and present; and major events in legal history and major debates in legal theory